Professional Learning Through Video: Reflection of a Pre-Service Teacher One Year On - Impedovo, Maria Antonietta; Cheneval-Armand, Helene (Alberta Journal of Educational Research, 2017)
The research presented in this paper investigates a pre-service teacher’s reflection on professional learning using the medium of video. To promote a reflective activity, we invited the pre-service teacher—now a titular teacher—to comment on their activity while remarking on a recording of one of theirlessons conducted one year earlier. The lesson was performed in a professional high school, followed by a meeting with the teacher and a university tutor. Quali-quantitative analysis was used to analyse the data--where the teacher’s reflections emerged during their viewing of the lesson—to trace the typology of the comments of the pre-service teacher, and the topics of the reflection. The analysis highlights the dimensions of reflective activity, which can be a reflection of the professional learning of the pre-service teacher in one year. This study provides useful information in describing the process of professional learning and, at the same time, supports the integration of video into pre-service teacher training as a tool of reflection. La recherche présentée dans cet article vise à étudier la réflexion d'un enseignant en formation sur son apprentissage professionnel en utilisant le milieu de la vidéo. Afin de promouvoir une activité de réflexion, nous avons invité un enseignant en formation – maintenant enseignant titulaire - à verbaliser sur son activité pendand une leçon enregistré un anné plus tôt. La leçon a été réalisée dans un lycée professionnel, suivie d'une rencontre avec l'enseignant titulaire et un tuteur universitaire. L'analyse quali-quantitative est utilisée pour analyser les données - toutes les réflexions des enseignants que sont émergé lors de la vision de la leçon - tracer la typologie des commentaires de l'enseignant, et les ses réflexions. Cette étude fournit des informations utiles pour décrire le processus d'apprentissage professionnel et, dans le même temps, soutenir l'intégration de la vidéo dans la formation initiale des enseignants comme outil de réflexion.